Integrating Building Information Modeling (BIM) and Unmanned Aerial Vehicle (UAV) for Building 3D Modeling: A Case Study of Wisma Sri Mahkota Bengkalis (CSID Journal of Infrastructure Development, 2022)
The demand for geospatial information of a region grows in numerous sectors, as does the method of mapping operations. Various advanced technology has been utilized to support survey and mapping activities, including Unmanned Aerial Vehicles (UAVs). This study aims to develop a method to digitize building documentation by integrating the UAV in the Building Information Modelling (BIM) by considering a lodging property in Bengkalis regency as the case study. Orthophoto data obtained from processing aerial photos taken using three flight paths, namely Nadir, Oblique, and Circular, was used to develop the BIM 3D model. The accuracy of the developed BIM model was evaluated using the orthophoto data as the horizontal accuracy using the Root Mean Square Error (RMSE) metrics. The accuracy calculation of Point Cloud 3D resulted from the integration of BIM and UAV, resulting in RMSExy of 0.0834 m, a height ratio of 0.05, and Circular Error (CE) accuracy of 0.1265 m included in the Level of Detail (LOD) 3, confirming the high accuracy of BIM-UAV integration.